Services Trade and Global Value Chains - Heuser, Cecilia; Mattoo, Aaditya (World Bank, Washington, DC, 2017)
Services play a role in global value chains in many ways, similar to goods. But services deserve special attention because of how they are transacted, how they affect downstream sectors, how they are regulated, and how international cooperation can contribute to integrating national markets. Databases on trade in value added, which cover only cross-border transactions in services, reveal a high and growing share of services in trade in value added across countries and industries. Although international transactions in services that take place through foreign investment are difficult to measure, their economic impact can be estimated. The resulting improved access to financial, communications, and transport services facilitates the emergence of global value chains, enhances downstream manufacturing firms’ productivity, and shifts the pattern of comparative advantage toward sectors intensive in these services. Despite significant unilateral liberalization, service markets in many countries remain protected by restrictions on the entry of foreign services and service providers, as well as discretionary and discriminatory regulatory requirements. International cooperation in services has attempted to follow the example of reciprocal market opening for goods, but this approach has delivered little incremental liberalization. More could be achieved through greater emphasis on international regulatory cooperation.